EQ-1 Quarantine Action for Horses Originating from Countries with different Health Status to EDFZ Jakarta for the 18th Asian Games 2018 - . Mujiatun; Risma Juniarti Paulina Silitonga; Agus Sinanto; . Sriyanto; Susanne Munstermann; Tri Wahyuni; . Deniswaty; Nuryani Zaenuddin; Arum Kusnila Dewi; Adi Komara; Woro Wulandari Kalanjati; Yasmin Qurotaayunina; Seruni Agistiana; . Haeriah; Hestu Prastanti; Dwi Indah Anjarsari; Lidwina Anastasya; . Ashari (Hemera Zoa, 2018)
Indonesia hosted the 18th Asian Games on 18 August to 2 September 2018. In order to organize the equestrian competitions of these Asian Games, an Equine Disease Free Zone (EDFZ) was set up. EDFZ is a term used by the World Organisation for Animal Health (OIE) for a specific zone in which equestrian competitions can be organized. This system is based on the OIE’s concept of compartmentalisation and zoning. A specified area is shown to be free from a defined list of equine diseases that are otherwise present in the country or region. Horses within an EDFZ are protected from diseases that may occur in other parts of the country (OIE 2018).Once the EDFZ is established, implementation of biosecurity management, health certification standards and procedures have to be observed, including the setting up of a Registered Animal Quarantine Installation (RAQI) to prevent the spread of diseases to this EDFZ.Horses that came from countries that have a disease situation equal to the EDFZ with specific health requirement such as vaccination and testing, were taken directly to the EDFZ core zone, which was the venue for the equestrian events at the Jakarta Equestrian Park, Pulomas [DGLAHS, 2018].  Few horses came from countries with a health status not equal to the EDFZ. These horses had to be quarantined in their country of residence for 21-30 days and again in Indonesia for 14-21 days. Based to the regulations of the Indonesian Agriculture Quarantine Agency (IAQA) a RAQI was set up to observe the health status of these horses.General observation of horse health status in the RAQI consisted of inspection for clinical signs of infectious diseases and also a repeat of laboratory testing for specified diseases which, as per requirement of the “Veterinary Certificate for the Temporary Importation of horses into Indonesia to compete in the equestrian events of the 18th Asian Games” (here: Asian Games Health Certificate), had already been tested in the country of residence.The purpose of this paper is to describe the quarantine action for horses in the RAQI at the 18th Asian Games 2018.